Carbon Nanospheres: Tunable Luminescent Carbon Nanospheres with Well‐Defined Nanoscale Chemistry for Synchronized Imaging and Therapy (Small 36/2015). Issue 36 (September 2015) - Mukherjee, Prabuddha; Misra, Santosh K.; Gryka, Mark C.; Chang, Huei‐Huei; Tiwari, Saumya; Wilson, William L.; Scott, John W.; Bhargava, Rohit; Pan, Dipanjan
<x xml:space="preserve">Abstract</x> Drug (PTX)‐loaded luminescent carbon nanoparticles (LCNs) are passivated with a thermoresponsive polymer (PNIPAM) inside melanoma cells. On page 4691, R. Bhargava, D. Pan, and co‐workers acquire such images using confocal fluorescence techniques. A representative cartoon of the nanoparticles is shown in black, where the white and the green shells represent the anti‐cancer drug (PTX: molecular structure shown) and the PNIPAM coating, respectively. The cells, upon internalizing the particles under physiological conditions, trigger the delivery of drugs contained in them.